Two decades of the Eurotransplant Senior Program: the gender gap in mortality impacts patient survival after kidney transplantation - Schachtner, Thomas; Otto, Nathalie M.; Reinke, Petra (My University, 2020)
Background. Long-termoutcomes of the Eurotransplant Senior Program (ESP) are urgently needed to improve selection criteria and allocation policies in the elderly. Methods. We analysed patient and allograft outcomes of 244 ESP-kidney transplant recipients (KTRs) between 1999 and 2019 and assessed quality of living compared with 82 ESP-waitlisted dialysis patients using standardized short form-8. Results. We observed 1-, 5- and 10-year patient survival of 91.7, 66.3 and 38.0%, respectively. Mortality risk factors included male gender (P¼0.006) and T-cell-mediated rejection (P<0.001). Median patient survival of male ESP-KTRs was 80 versus 131months for female ESP-KTRs (P¼0.006). 1-, 5- and 10-year death-censored allograft survival was 93.3, 82.6 and 70.4%. Risk factors included high body mass index (P<0.001) and T-cell-mediated rejection (P<0.001). After re-initiation of dialysis median patient survival was 58 months. Change of estimated glomerular filtration rate showed a mean decline of 2.3 and 6.8 mL/min at 5 and 10 years. Median physical and mental component scores of ESP-KTRs were 40.2 and 48.3, significantly higher compared with dialysis patients (P<0.05). Of ESP-KTRs, 97.5% who underwent transplantation would again do so. Conclusions. Long-term outcomes of ESP-KTRs ultimately support the effectiveness of an age-matched allocation system. Our data suggest that the survival advantage of women is maintained after kidney transplantation and calls for genderspecific care.
Keywords: Geschlechterdifferenz; Medizin; Alter; 610 Medizin und Gesundheit; Gender Health Gap